Case Report: Sudden cardiac death due to spasm of multiple coronary arteries - JiaQi Tang; YanDan Xu; MingLei Zhang; ChenChen Wang (Frontiers in Cardiovascular Medicine)
Diffuse coronary artery spasm (DMV-CAS) is a serious vascular condition characterized by prolonged narrowing of two or more major coronary arteries or their main branches, leading to significant stenosis or blockage (≥70%). This can result in myocardial ischemia, heart attacks, and dangerous arrhythmias. A 68-year-old male with a four-year history of recurrent angina presented with acute-onset chest tightness, palpitations, and syncope. During transport, the patient experienced prehospital cardiopulmonary arrest, with transient return of spontaneous circulation (ROSC) achieved in the emergency department. Electrocardiographic evaluation revealed atrial fibrillation with rapid ventricular rate, pathological Q waves in the inferior, anterior, and anterior septal territories, along with dynamic ST-T abnormalities, including ST elevation in leads II, III, aVF, and V1-6, and ST depression in leads I and aVL. Emergent coronary angiography identified critical multivessel stenoses, with the most significant narrowing observed in the left anterior descending artery. The diagnosis of DMV-CAS was corroborated through angiographic evidence, demonstrating resolution of the spasm following the administration of intracoronary nitroglycerin (200 μg administered bilaterally to the coronary arteries). Despite the implementation of targeted vasodilator therapy, the patient progressed to refractory cardiogenic shock and succumbed in the intensive care unit 1 h after the procedure. This case underscores the rare and severe cardiovascular implications of DMV-CAS, emphasizing the critical need for early and accurate diagnosis of DMV-CAS and the necessity for standardized pharmacological intervention.